Match play intensity distribution in youth soccer - Mendez-Villanueva, A.; Buchheit, M.; Simpson, B.; Bourdon, P. C. (International Journal of Sports Medicine, 2013)
The purpose of this study was to quantify match play intensity distribution in young soccer players in relation to age, playing position and physical fitness. Distance covered and heart rate were measured (global positioning system) on 103, highly-trained young players (Under13 to Under 18) during 42 international club games. Maximal sprinting speed (MSS), estimated maximal aerobic speed (MAS) and maximal heart rate (HRmax) were assessed via field test measures. Distance covered and heart rate (HR) were categorized into 5 intensity zones relative to MSS and MAS and HRmax, respectively. Intensity distribution was significantly influenced by both age and playing position with younger groups, wide-midfielders and strikers covering the greatest distance above the MAS. There was a significant, negative, large-to-very large correlation (r= - 0.52-0.74) between MAS and the distance run at speeds above MAS for all positions except strikers. HR responses were not different across age groups and playing positions. Distance covered below MAS were lower in the second half for all positions (P<0.05; 0.08<?2<0.20), while distance covered at intensities above MAS were maintained (P>0.1; 0.00<?2<0.03). This reduction in distance covered below MAS was not related to a player's physical capacity. Except for strikers, a superior aerobic fitness level was unlikely to affect total distance covered but was associated with a reduced individual running demand during the game.